Problematika Perizinan Penguasaan Senjata Api Teramunisi Untuk Sipil Dalam Perspektif Hukum Positif Nasional - Syabilal Ali; Emaeve Nur Berliantari; Aslihatin Zuliana; Irwan Triadi (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Firearms are a big problem when their use can be regulated for civil society, because simply a freedom with big risks will cause other big problems. Providing a sense of security and personal protection by giving rise to abuse will certainly create confusion both for those who regulate it and those who will clearly feel the dangerous impact. This research aims to determine the factors, efforts and obstacles in tackling the crime of possessing firearms without a permit. The research method used in this research uses a normative juridical research approach with a problem approach using a statutory approach. The findings in this research are that a person's internal and external factors greatly influence the efforts that can be made to prevent and overcome criminal acts of possession of firearms and from all forms of efforts made, various obstacles are also found that are present, from the government's quick response in dealing with it to low awareness. the community has an important role in overcoming these legal issues.